Trade Liberalization Policy and Competitiveness of Cocoa Beans Exports in Nigeria (1961-2017) - Obi-Egbedi, Ogheneruemu; Hussayn, Jamiu; Oluwatayo, Isaac (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2021)
The cocoa sector in Nigeria has experienced decline in production, yield, exports coupled with its inability to attain global standards and targets and, gradual loss of competitiveness at the world market. Trade liberalization was government’s panacea to the sector’s problem although, cocoa competitiveness remains an issue since liberalization. Therefore, the relationship between trade liberalization policy and competitiveness of Nigeria’s cocoa exports was examined in this study using data for the period 1961-2017. Cocoa market share was used to measure competitiveness while analytical tools employed were: ADF test, Johansen co-integration test and the vector error correction model (VECM). Market share, quantity of cocoa export and inflation rate were stationary at original level while others, at first difference. The co-integration test showed seven co-integrating equations. Trade liberalization policy was found to be an important driver of competitiveness. In addition, area harvested, production quantity and export quantity positively influenced competitiveness while world price of cocoa, interest rate on agricultural loans, exchange rate and trade liberalization influenced negatively. Therefore, appropriate trade policy formulation and implementation is recommended while, specific attention should be paid to monetary policies and cocoa production by the government.